2012
DOI: 10.3139/113.110223
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Surface Properties of CO2H Type Gemini Surfactant Having Semifluoroalkyl Group as Hydrophobic Group

Abstract: Novel CO2H type gemini surfactants having semifluoroalkyl group (Rf-(CH2)n-: Rf = C4F9, C6F13, C8F17 and n = 2, 3) as hydrophobic group were successfully synthesized and their surface properties were studied. (Perfluoroalkyl)ethylmalonic esters were synthesized by the reaction of malonic ester with Rf(CH2)2I using NaH as base in THF/DMF. (Perfluoroalkyl)propylmalonic esters were synthesized from allylmalonic ester, namely by the radical addition of Rf-I using AIBN as initiator, and reduction with Zn/AcOH. Thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…In fluoroalkylated gemini surfactants, fluoroalkyl groups are introduced into the tail segment; this is generally achieved by radical addition of a perfluoroalkyl iodide to a H 2 C CH-group, as described by Brace 17 . In our previous study 14 , CO 2 H-type malonic acidbased gemini surfactants containing semifluoroalkyl groups Rf-CH 2 n -; Rf C 4 F 9 , C 6 F 13 , C 8 F 17 and n 2, 3 and -CH 2 s -spacers s 3, 4 were successfully synthesized via the connection of Rf-CH 2 3 -malonic esters, which were synthesized by radical addition of Rf-I to the H 2 C CH-CH 2 -moiety of allylmalonic ester, followed by reduction with Zn/AcOH, linking with Br CH 2 s Br s 3, 4 to tetraesters, and then hydrolysis and decarboxylation. In this synthetic route, the introduction of the fluoroalkyl group into the tail segment is the initial step.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fluoroalkylated gemini surfactants, fluoroalkyl groups are introduced into the tail segment; this is generally achieved by radical addition of a perfluoroalkyl iodide to a H 2 C CH-group, as described by Brace 17 . In our previous study 14 , CO 2 H-type malonic acidbased gemini surfactants containing semifluoroalkyl groups Rf-CH 2 n -; Rf C 4 F 9 , C 6 F 13 , C 8 F 17 and n 2, 3 and -CH 2 s -spacers s 3, 4 were successfully synthesized via the connection of Rf-CH 2 3 -malonic esters, which were synthesized by radical addition of Rf-I to the H 2 C CH-CH 2 -moiety of allylmalonic ester, followed by reduction with Zn/AcOH, linking with Br CH 2 s Br s 3, 4 to tetraesters, and then hydrolysis and decarboxylation. In this synthetic route, the introduction of the fluoroalkyl group into the tail segment is the initial step.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the synthesis of malonic acid-based gemini compounds 14 , dilactone diesters 7 were hydrolyzed under alkaline conditions using excess KOH; after acidification, the precipitates were collected. The IR spectra showed that the products were mixtures of butyrolactones and γ-hydroxybutyric acids.…”
Section: Synthesis Of Gemini Dilactones 11mentioning
confidence: 99%
See 1 more Smart Citation
“…The prolonged heat of the same reagents 2 with a zinc excess, yield the bis(vinyl perfluoroalkyl) oxyethylene 6 as exclusive products. The highly fluorinated obtained compounds 2-perfluoroalkyl acids 3 and bis(vinyl perfluoroalkyl ester) ethoxides 6, among many others applications, may have interesting surface properties [64][65][66] and can also undergo some interesting reactions, particularly in the synthesis of organofluorinated heterocyclic compounds [67,68] …”
Section: Resultsmentioning
confidence: 99%
“…Such compounds are used as surfactants [17][18][19][20], agrochemicals [21,22], pharmaceutical [23][24][25][26][27], biological [28] and medical agents [29,30]. While they are detected in human bodies [31,32], municipal water and solid wastes in different industrial areas around the world [33][34][35] and considered as high polluter for environment and toxic compounds [36,37], perfluoroalkyl acids are interesting compounds used as tensioactifs [38][39][40], fire-fighting foam [41][42][43], fluoropolymers [44] and other important applications.…”
Section: Introductionmentioning
confidence: 99%